Hrabianki Szembekówny - pionierki archeologii wielkopolskiej z przełomu XIX i XX wieku - Fogel, Jerzy (Folia Praehistorica Posnaniensia, 2018)
Archaeological interests of the Szembek earls from Siemianice near Kępno (southern Wielkopolska) have spread over many generations starting from the middle of the 19th century until the present time. This is well exemplified by activities of Jadwiga (1883-1939) and Zofia (1884-1974) Szembek. In the years 1897-1908, both sisters undertook systematic and model excavations of the multicultural cemetery (-ies) at Siemianice near Kępno (Bronze Age 11, Bronze Age V - HaD; the Late La Téne - Early Roman Iron Age) and cemetery at Lipie near Kępno (Bronze Age V). Jadwiga Szembek excavated also multicultural settlement at Tarnowica near Jaworów (western Ukraine) in 1924 and 1927. An origin and development of archaeological interests of the Szembek sisters, along with a detailed analysis of their field works, was reconstructed on the basis of unpublished archive materials and old literature of the subject. Assessment of their achievements in this field, according to both previous and current criteria, made possible to support opinion by Prof. Józef Kostrzewski who rated the Szembek sisters among archaeologists of the most outstanding merit before 1918.